Effects of inspiratory muscle training on lung function parameter in swimmers: a systematic review and meta-analysis - Carvajal-Tello, Nathali; Ortega, José Guillermo; Caballero-Lozada, Andrés Fabricio; Devia-Quiñonez, María Juliana; González-Calzada, Isabella; Rojas-Hernández, Daniela; Segura-Ordoñez, Alejandro (Frontiers in Sports and Active Living, 2024)
Background: This systematic review and meta-analysis aimed to assess the impact of inspiratory muscle training (IMT) on lung function parameters (MIP, MEP, FEV1, and FVC) between both elite and non-elite swimmers.We searched for controlled clinical trials (CCT) and prospective longitudinal studies (PLS) in elite and non-elite swimmers following an inspiratory muscle training (IMT) protocol with a standardized device, published between 2012 and 2023. The databases used in the search were PubMed, Science Direct, Scopus, Springer, Cochrane Central Register of Controlled Trials, and Google Scholar. The primary outcome assessed was the impact of IMT on lung function parameters, including MIP, MEP, FEV1, and FVC.We selected 13 articles involving 277 subjects aged 11 to 21 years, with 61.4% being male, and 84.6% being elite swimmers. The most commonly used IMT device was the PowerBreathe®, prescribed for 3 to 12 weeks, 1 to 2 sessions per day, 3 to 6 times per week, with 30 repetitions, starting at 50% of MIP and progressing up to 80%. The meta-analysis showed that IMT was associated with a higher MIP (MD = 29.35 cmH2O, 95% CI: 13.04 to 45.65 cmH2O, p < 0.01) without affecting FEV1 and FVC. The swimmers that used IMT improved muscle strength, specifically MIP, without changes in MEP, FEV1, and FVC.